2009
DOI: 10.1080/00206810902945090
|View full text |Cite
|
Sign up to set email alerts
|

Sulphur- and lead-isotope geochemistry of the Arapuçandere lead–zinc–copper deposit, Biga Peninsula, northwest Turkey

Abstract: The Arapuçandere Pb-Zn-Cu ore body is a typical vein-type lead -zinc deposit of the Biga Peninsula, and is currently being mined for lead and zinc. In the study area, Permian-Triassic metamorphic rocks, Triassic metaclastic and metabasic rocks, Oligocene -Miocene granitoids, Miocene volcanic rocks, and Quaternary terrigenous sediments crop out. The ore deposits developed as Pb-Zn -Cu-bearing veins along faults in Triassic metasandstone and metadiabase. Microscopic studies reveal that the veins contain galena, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 12 publications
0
13
1
3
Order By: Relevance
“…The sulfide minerals of ores formed in deposits usually contain very low concentrations of U and Th and insignificant increase of the radiogenic Pb (Zhang, 1992;Zhang & Gao, 2012). Therefore, Pb isotopes of sulfides from deposits are commonly used to constrain the source of the Pb, regardless of the total Pb concentration in the sulfides (e.g., Bozkaya, 2011;Goldfarb et al, 2004;Mortensen et al, 2008;Zhao, Jiang, Ni, Ling, & Jiang, 2007).…”
Section: Lead Sourcesmentioning
confidence: 99%
“…The sulfide minerals of ores formed in deposits usually contain very low concentrations of U and Th and insignificant increase of the radiogenic Pb (Zhang, 1992;Zhang & Gao, 2012). Therefore, Pb isotopes of sulfides from deposits are commonly used to constrain the source of the Pb, regardless of the total Pb concentration in the sulfides (e.g., Bozkaya, 2011;Goldfarb et al, 2004;Mortensen et al, 2008;Zhao, Jiang, Ni, Ling, & Jiang, 2007).…”
Section: Lead Sourcesmentioning
confidence: 99%
“…Sıvı kapanım çalışmalarıyla elde edilen veriler sayesinde akışkanların yüksek tuzluluklu (olasılıkla magmatik) sıvılar ve meteorik sıvıların etkileşimleri sonucu oluştuğu ortaya koyulmuştur. Bozkaya (2011), δ 34 S ve Pb izotop çalışmaları ile sıvı kapanım verileri yardımıyla Arapuçandere Pb-Zn-Cu damarlarındaki Pb ve S'ün Erken Kretase-Paleosen aralığında derin dolaşımlı meteorik sular aracılığı ile Triyas yaşlı metaklastik ve metabaziklerden süzülerek zenginleştiğini ifade etmiştir. Ancak, tüm bu modellerde hala açıklanmayı bekleyen noktalar bulunmaktadır.…”
Section: Tartişma Ve Sonuçlarunclassified
“…Lead isotope signatures can be used to define the source of Pb (Doe & Zartman, ), and to fingerprint mineral systems with model age information for an individual deposit (Downes & Seccombe, ). Therefore, the application of lead isotope analysis can provide important data to be used in constraining the process of ore formation (Harkins, Appold, Nelson, Brewer, & Groves, ; Zartman & Smith, ; Bozkaya, ; Huston, Pehrson, Eglington, & Zaw, ; Huston, Relvas, Gemmell, & Drieberg, ). A limited previous work dealing with lead isotopic characteristics for the well‐known and sizeable volcanic‐hosted massive sulfide (VHMS) deposits concluded that the source region of the VHMS deposits has a variety of tectonic settings, with a range in lead isotope composition, consistent with variable contributions of lead from the mantle, seawater, and sediments (Fouquet & Marcoux, ; Stuart, Ellam & Duckworth, 1999; Hannington, De Ronde, & Petersen, ; Huston et al, ).…”
Section: Introductionmentioning
confidence: 99%